2020
DOI: 10.3390/beverages6020034
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of the Effects of Pulsed Electric Field (PEF) Treatments in Wines Obtained from Early-Harvested Sangiovese Grapes

Abstract: In this experiment, the effect of pulsed electric field (PEF) technology on the extractability of anthocyanins and polyphenols in early-harvested Sangiovese red grapes (16.9°Bx sugar, 3.26 pH, and 10.4 g/L titratable acidity) from Emilia Romagna (Italy) was investigated. Electric field strengths were in the range of 0.9–3 kV/cm, generated by the application of short, high-voltage pulses, and the grapes were subjected to specific energies from 10.4 to 32.5 kJ/kg immediately after crushing and destemming to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Before the use of water addition becomes more widespread as a means to alleviate issues with high TSS musts, research could also continue to focus on the consequences of water addition across a wider range of varieties which are relevant to Australian production, for example white grape varieties such as Chardonnay. Furthermore, for red winemaking, alternative maceration strategies such as ultrasound, pulsed electric field or “accentuated cut edges” (ACE) [ 28 , 29 , 30 , 31 ] could be explored, which might improve the phenolic concentration and sensory profile of wines made from less mature fruit. Hence, wine alcohol might be reduced by simply harvesting earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Before the use of water addition becomes more widespread as a means to alleviate issues with high TSS musts, research could also continue to focus on the consequences of water addition across a wider range of varieties which are relevant to Australian production, for example white grape varieties such as Chardonnay. Furthermore, for red winemaking, alternative maceration strategies such as ultrasound, pulsed electric field or “accentuated cut edges” (ACE) [ 28 , 29 , 30 , 31 ] could be explored, which might improve the phenolic concentration and sensory profile of wines made from less mature fruit. Hence, wine alcohol might be reduced by simply harvesting earlier.…”
Section: Discussionmentioning
confidence: 99%
“…PEF is a green technology that can improve phenol extraction from branched starch of blueberry pomace [82] and can increase the concentration of phenolic compounds in olive pomace [83]. Ricci et al [84] found that a mild PEF can also be applied to reduce the accumulation of bioactive compounds in plants to obtain commodities with health-promoting properties. López-Gámez et al [85] found that the timing of PEF treatment of postharvest carrots affected their compound content, respiration rate, volatile organic compound production, and enzyme activity, with a significant 24 h posttreatment regime, accompanied by a significant increase in total phenolic content (80.2%).…”
Section: Pulsed Electric Field (Pef) Methodsmentioning
confidence: 99%
“…The colour intensity (CI) of wine samples during the winemaking process was measured as the sum of absorbances at 620, 520 and 420 nm and calculated as a relative percentage of yellow, red, and blue (%Yl, %Rd, %Bl), while colour hue (CH) defined as absorbance ratio at 420 and 520 nm [5,6]. Additionally, for selected samples (1C, 2C, 3-6) the brilliance of wine was calculated: (100•(1 − (A 420 + A 620 )/2• A 520 )).…”
Section: Determination Of Selected Wine Quality Parametersmentioning
confidence: 99%